Simulaciones de políticas antiinflacionarias en Argentina, 1983/87 - Jaksch, Hans J. (1986)
In this paper, we present a small econometric model and simulate with it some possible consequences of the Argentine monetary reform of June 14, 1985. First, we derive some theoretical properties of the nonlinear recursion model consisting of three equations. Second, results obtained when estimating this model by the ordinary least squares and the full information maximum likelihood method are presented. Finally, we use the estimated model for deterministic and stochastic ex ante predictions. The result is that a reduction of the deficit in the budget of the Argentine government which is financed by creating money is of paramount importance in order to stabilize the price level. If by February 1987, the horizon of the simulations, this deficit cannot be again reduced to 2.5 percent of the gross domestic product of or less, the stabilization of the Argentine currency appears to be impossible, while otherwise there exist prospects that the stabilization program will be successful.